IEEE 1901.1 Power Line Communication electromagnetic emission study. Issue 1 (July 2021) - Amaro, Nuno; Saragoça, João; Cartaxo, Ricardo; Yang, Wei; Yi, Ren
Abstract: IEEE 1901.1 Standard for Medium Frequency (less than 12 MHz) Power Line Communications for Smart Grid Applications was officially released in 2018. This standard expands the possible applications of Power Line Carriers communications by using a medium frequency technology, allowing for a higher bandwidth and bit rates compared to the current industrially used solutions. As the standard operates below a frequency of 12 MHz, and constituting a new solution in this area, it is fundamental to evaluate electromagnetic emissions and evaluate possible electromagnetic disturbances. In this paper, we pre-sent a methodology to measure electromagnetic emissions of IEEE1901.1 compatible devices. This methodology is then used to measure real emissions from two different IEEE compliant modules from two different manufacturers, including central coordinator and station devices.